Caracterización de las Propiedades Fisicoquímicas y Térmicas de Almidón extraído de papa nativa (solanum tuberosum l.), variedad “manzana”, cultivada en el Distrito de Chugay, Provincia de Sánchez Carrión, Departamento de La Libertad. - Bejarano Cruz, Rodrigo Santiago (2017)
The objective of this research was to determine the shape and size of the granules, apparent amylose content, swelling power, solubility, clarity of the paste, gel strength, stability in refrigeration and freezing, temperature and enthalpy of gelatinization of native potato, variety “Manzana”. The size of the granules was found in the range of 4.03±1.59 a 73.61±17.97 μm and showed the circular shapes for small sizes and elliptical for large sizes. Showed low swelling power and solubility values, those were increased with the increase of temperature; high transparency (44.07±1.99%), low firmness (13.28±0.19 g), low stability in freezing (57.24±0.93% a 42.61±2.09%) and low temperatures of gelatinization (T0: 59.93±0.20 °C; Tp: 62.95±0.12 °C; Tf: 67.84±0.15 °C) and ΔH: 13.76±0.15 J/g. By the properties evaluated may be considered to be used in products that do not require high temperature processing, such as candy or custards, such as thickeners and stabilizers in those foods that need to be stored refrigerated (4 °C) and need some oozing of moisture to provide a fresh appearance, such as custards and sauces.